Literary heritage of the great Babur - Sobirov Jamshidbek Zokirjon oglu, (Global Scientific Publishing, 2022)
The article speaks about the fact that the great commander Zahiriddin Muhammad Babur was not only a king, but also a scholar and poet, as well as the great literary legacy of Mirzo Babur.
Keywords: Mirzo Bobur; Boburnoma; Navoi; ghazal